Métodos de investigación jurídica: Análisis de su diversidad y fundamentos epistemológicos: Legal research methods: analysis of its diversity and epistemological foundations - Obando-Peralta, Ena Cecilia (Political Questions, 2025)
Legal research has had difficulties in explaining the nature of its activities during the act of inquiry, because the environment surrounding the practice of law is complex, interdisciplinary and, at the same time, derives in the generation of new knowledge for the balance of the administration of justice in the face of social reality. By virtue of the above, the article aims to analyze the epistemological and gnoseological implications of legal research, its typological nature and the essence that links it to the scientific method of research in general. The research makes use of the hermeneutic-documental analysis of the social phenomenon, with the purpose of relating the aspects studied with the fair application of investigative law. To achieve this task, the linkage of legal research was studied, making use of the reference and implications of the epistemological, typological, and methodological scientific qualities in an environment that requires systematic, rigorous and verifiable procedures, since it generates new constructions of jurisprudential knowledge. As a proposal, the use of emerging technologies in legal research is recommended as a tool to provide efficiency in the face of new problems that occur in the research processes.